Zwrot świadczeń nienależnych w prawie ubezpieczeń społecznych — wybrane zagadnienia - Napiórkowska, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The article refers to the selected issues of the recovery of undue benefits in the social insurance scheme. Initially, the subject matter of the analysis is the recent modification of the art. 84 of the Act of 13 October 1998 on the social insurance system. It is argued in the article that there are not persuasive arguments why the recent change — introducing the limit for handing down adecision for the Polish Social Insurance Institution art. 84 [7a] of the Act on the social insurance system — does not relate to the contribution payer or the other persons enumerated in the art. 84 6 of the Act on the social insurance system. Furthermore, the paper analyses the notion of the undue benefit in the social insurance scheme and the issues of the instruction. In the article there are emphasized some questions referring to the explanatory proceedings conducted by the Polish Social Insurance Institution ZUS and the issues of the relations between the art. 84 1 and 6 of the Act on the social insurance system. In the conclusion the article analyses the relations between the art. 84 of the Act on the social insurance system and the special regulations, i.e. art. 138 of the Act of 17 December 1998 on pensions from the Social Insurance Fund and art. 66 of the Act of 25 June 1999 on cash social insurance benefits in respect of sickness and maternity
Keywords: prawo socjalne; świadczenia nienależne; zwrot